Visual effects and video analysis lead to Olympics victories - Sheppard, L. M. (IEEE Computer Graphics and Applications, 2006)
In one study, researchers at several universities and the US Olympic Committee compared triple and quadruple toe loops by using high-speed video and 3D analyses at the 2002 Salt Lake City Winter Olympics. Researchers created 3D models of the skaters using motion capture from video taken with special camera systems during competitions. To capture a skill from anywhere on the rink, calibration of the whole ice rink was required prior to each day of testing. This involved testing with two survey poles, each 4.88 meters long, sequentially moved to seven locations on the ice. Combinations of three to five poles that gave the best 3D reconstruction were used to establish calibrations for each day of data collection. The 3D reconstruction error was determined by computing the root mean square difference between the actual and computed distances of ice and board markings and the poles not included in the calibrations. http://libgen.org/scimag/get.php?doi=10.1109/MCG.2006.50